Detailed investigation of submicrometer-sized grains of chemically sprayed (Sn1-xAlx, O2) (0 ? x ? 0.085) thin films - Benhaliliba, M.; Benouis, C. E.; Yakuphanoğlu, Fahrettin; Tiburcio-Silver, A.; Aydin, C.; Hamzaoui, S.; Mouffak, Z. (Elsevier Science Sa, 2012)
In this study, the submicrometer-sized grains of chemically sprayed tin oxide, SnO2, were largely investigated. The films (Sn1-xO2, Al-x), with x = 0-0.085 were grown by spray pyrolysis onto glass at a fixed temperature of 300 degrees C. Structural, optical, electrical and morphological properties were studied. These films are polycrystalline in nature with a tetragonal crystalline structure, and exhibited a preferred orientation along the (2 0 0) planes. Atomic force microscope (AFM) analysis demonstrated a nano-grain structure. Our nanostructured films revealed high transparency in the visible and infra-red spectra and an electrical resistivity that ranged from 1 to 1000 Omega cm. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Tin oxide; Spray pyrolysis; Al doping; Physical properties; Submicrometer structure; AFM